In vivo comparison of hard tissue regeneration with ovine mesenchymal stem cells processed with either the FICOLL method or the BMAC method. Issue 7 (September 2015) - Ardjomandi, N.; Duttenhoefer, F.; Xavier, S.; Oshima, T.; Kuenz, A.; Sauerbier, S.
Abstract Introduction The aim of this work was to analyse the suitability of mesenchymal stem cell isolation by FICOLL density centrifugation and the closed bone marrow aspirate concentrate (BMAC) system for sinus augmentation with bovine bone mineral (BBM) in the sheep model. Methods 16 sheep underwent sinus augmentation with BBM and MSCs; they were divided between two groups with survival points of 8 and 16 weeks. For the FICOLL control arm three, and for the BMAC test arm, five augmentations were performed for each time point. The derived cell numbers were counted; a colony forming unit (CFU) assay was performed; the pluripotency of the MSCs was proved; histological and histomorphometrical analysis were performed. Results The approach of using BBM and MSCs in combination with fibrin adhesive was sufficient for new bone formation as the FICOLL experiment indicated. However, due to significantly lower cell numbers isolated using the BMAC in sheep, less new bone was formed in the test arm. Conclusions The BMAC system is well suited for human MSC isolation but it needs to be optimized to fit sheep cell characteristics if it is to be used in this animal model.